DEKA protocols for meta-analyses: Strengthening study transparency through a modified PRISMA approach - Fajar, Jonny (PT. DEKA RESEARCH INSTITUTE, 2025)
Meta-analysis has emerged as an increasingly vital method for synthesizing scientific evidence in support of data-driven decision-making. To maximize its contribution, meta-analysis manuscripts must be written in a systematic and informative manner. This article aims to provide a conceptual and technical guide on how to write a meta-analysis article that adheres to international scientific standards. In reporting meta-analyses, the title serves as a critical entry point for both readers and reviewers; therefore, it should clearly reflect the population, intervention, and outcome of interest, and include the phrase “a systematic review and meta-analysis” to facilitate indexing. An effective abstract should be concise and well-structured, encompassing the background, objective, methods, main findings, and conclusion, while maintaining clarity and self-sufficiency. The selection of keywords is equally important, as it significantly enhances article visibility in scientific databases; thus, the use of Medical Subject Headings (MeSH) is strongly encouraged. The introduction should present a logical framework that outlines the broader research issue and the specific covariates under analysis, along with clearly formulated objectives and hypotheses. The methods section must transparently describe the literature search strategy, inclusion and exclusion criteria, study quality appraisal, and statistical approaches, all aligned with PRISMA guidelines. Results should be reported systematically, with attention to heterogeneity, publication bias, and consistency of effects. The discussion should synthesize findings in relation to existing literature and theory, address study limitations, and identify directions for future research. The conclusion should highlight the clinical or scientific relevance of the main findings and outline opportunities for future exploration. When written in accordance with proper structure and scholarly principles, a meta-analysis article can achieve strong academic value and broad contributions to science and clinical practice.